If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 5) + 4x + -19 = 2x + 7 + -1(3 + -1x) Reorder the terms: 2(5 + x) + 4x + -19 = 2x + 7 + -1(3 + -1x) (5 * 2 + x * 2) + 4x + -19 = 2x + 7 + -1(3 + -1x) (10 + 2x) + 4x + -19 = 2x + 7 + -1(3 + -1x) Reorder the terms: 10 + -19 + 2x + 4x = 2x + 7 + -1(3 + -1x) Combine like terms: 10 + -19 = -9 -9 + 2x + 4x = 2x + 7 + -1(3 + -1x) Combine like terms: 2x + 4x = 6x -9 + 6x = 2x + 7 + -1(3 + -1x) -9 + 6x = 2x + 7 + (3 * -1 + -1x * -1) -9 + 6x = 2x + 7 + (-3 + 1x) Reorder the terms: -9 + 6x = 7 + -3 + 2x + 1x Combine like terms: 7 + -3 = 4 -9 + 6x = 4 + 2x + 1x Combine like terms: 2x + 1x = 3x -9 + 6x = 4 + 3x Solving -9 + 6x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -9 + 6x + -3x = 4 + 3x + -3x Combine like terms: 6x + -3x = 3x -9 + 3x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 -9 + 3x = 4 + 0 -9 + 3x = 4 Add '9' to each side of the equation. -9 + 9 + 3x = 4 + 9 Combine like terms: -9 + 9 = 0 0 + 3x = 4 + 9 3x = 4 + 9 Combine like terms: 4 + 9 = 13 3x = 13 Divide each side by '3'. x = 4.333333333 Simplifying x = 4.333333333
| Log(x)-log(x+3)=1 | | 1/2+3/2x+2/3-x/3=5/6 | | -2y^2+4y^3= | | 6x+x^2=55 | | 2x^2-34x=336 | | 6-6c=41 | | 120=(x+3)(x+1) | | 1/4d=12 | | -2(x-3)+10=4(5-4x) | | -5-c=25 | | -9b+3=-24 | | -24+6x=48 | | -4n+14=-2n-12 | | 20x^2+20x+20=0 | | 36=-8b-8 | | 33=-2y+25 | | 40=-6-5w | | 10-x=25 | | 900=120+(30+x) | | 8x-3x=-50 | | -5x+9+8x-7=-12 | | 900=120(30+x) | | Y-8=14(x+16) | | 14=-11-15b | | 3x-4/5+13/x=8/x+4 | | 900=12(30+x) | | (4.12+0.03)/0.05 | | 14*16= | | 8b+11=51 | | .316=2x/(0.04-x) | | x^4+7x^3+10x^2=0 | | 46-14=4(x-1) |